2018
DOI: 10.3390/mi9050236
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Research of a Novel Three-Dimensional Force Flexible Tactile Sensor Based on an Improved BP Algorithm

Abstract: Decoupling research on flexible tactile sensors play a very important role in the intelligent robot skin and tactile-sensing fields. In this paper, an efficient machine learning method based on the improved back-propagation (BP) algorithm is proposed to decouple the mapping relationship between the resistances of force-sensitive conductive pillars and three-dimensional forces for the 6 × 6 novel flexible tactile sensor array. Tactile-sensing principles and numerical experiments are analyzed. The tactile sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For instance, Song et al employed a backpropagation (BP) neural network to successfully decouple three-dimensional forces on a 6 × 6 flexible array touch sensor. 168 The sensor consists of numerous sensitive units, each with two upper tactile sensing electrodes at its top. When force components along the X and Z directions are applied to the sensor, the tactile sensor array undergoes deformation.…”
Section: Design and Construction Of Flexible Resistive Tactile Sensorsmentioning
confidence: 99%
“…For instance, Song et al employed a backpropagation (BP) neural network to successfully decouple three-dimensional forces on a 6 × 6 flexible array touch sensor. 168 The sensor consists of numerous sensitive units, each with two upper tactile sensing electrodes at its top. When force components along the X and Z directions are applied to the sensor, the tactile sensor array undergoes deformation.…”
Section: Design and Construction Of Flexible Resistive Tactile Sensorsmentioning
confidence: 99%
“…Additionally, Additionally, Wang et al [218] decoupled three-dimensional forces by radial basis machinelearning algorithm in ideal conditions. Moreover, Song and co-authors [219] demonstrated an efficient machine learning method based on back-propagation (BP) algorithm for flexible pressure sensor arrays. The BP algorithm mainly consists of two parts: information forward-propagation and error backward-propagation [220].…”
Section: Decoupling Calculation Models For Anti-interferencementioning
confidence: 99%
“…All of the connecting weights are continuously adjusting during the convergence process until the mean square error is less than the target value. In the work of Song's group [219], the k-cross validated BP models with different hidden nodes is used to calculate the force components for the tactile sensor. The n-dimensional vector including the resistances of the devices is regarded as the input for the BP model, and the m-dimensional vector consisting of force components was reckoned for the output.…”
Section: Decoupling Calculation Models For Anti-interferencementioning
confidence: 99%
“…One review [1] and four research articles [2,3,4,5] have been published in this Special Issue. These cover several topics in the field, spanning the recent technological advancements and the analysis of novel devices to the development of sensor network systems and improved algorithms as well as their clinical application on blind patients.…”
mentioning
confidence: 99%
“…Machine learning is becoming a useful and powerful tool for tactile sensing in soft systems. Song et al [4] faced the challenge of decoupling single components of three-axial force sensors by means of a machine learning method based on the improved back-propagation (BP) algorithm. This was applied in a 6 x 6 tactile sensor array to obtain the three-dimensional forces from the resistances of force-sensitive conductive pillars.…”
mentioning
confidence: 99%